Improving Students' Critical Thinking Skills in Learning Mathematics Using Problem Posing Approach - Pradnya Paramitha Solikhah; Abdul Haris Rosyidi; Endang Yayuk Sri Widiastuti (Jurnal Pendidikan Matematika (JPM), 2024)
This study aims to improve students' critical thinking skills in mathematics learning using a problem posing approach. This study was classroom action research conducted over two cycles. Researchers use tests of critical thinking skills and observation sheets for data collection techniques. The subjects of this study were 35 grade 8 students of SMPN 2 Candi. Data analysis techniques use a combination of qualitative and quantitative. The results of the study showed that based on the results of the critical thinking skills test, there was a significant increase in the percentage of classical completeness from the pre-action stage to cycle 1, and there was a slight increase from cycle 1 to cycle 2. In the pre-action stage, there were 68.57% of students completed, where students are said to complete if their level of mastery is in the category of sufficient or above. In cycle 1, 80% of students completed, and in cycle 2 there were 82.86% of students completed. Based on the study results, it was concluded that students' critical thinking skills in mathematics learning have increased by applying the problem posing approach.